2014
DOI: 10.1016/j.mce.2013.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic mutations of tumor suppressive genes in sporadic pituitary adenoma

Abstract: Human pituitary adenomas are the most common intracranial neoplasms. Approximately 5% of them are familial adenomas. Patients with familial tumors carry germline mutations in predisposition genes, including AIP, MEN1 and PRKAR1A. These mutations are extremely rare in sporadic pituitary adenomas, which therefore are caused by different mechanisms. Multiple tumor suppressive genes linked to sporadic tumors have been identified. Their inactivation is caused by epigenetic mechanisms, mainly promoter hypermethylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0
22

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 321 publications
1
68
0
22
Order By: Relevance
“…RASSF1 protein thus can modulate the balance of cellular growth via its competitive binding to RAS. The mutation or elimination of RASSF1 will facilitate RAS-mediated cellular growth, further causing tumor occurrence (Tse et al, 2013;Zhou et al, 2014). This may be one of the mechanisms of RASSF1-mediated oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RASSF1 protein thus can modulate the balance of cellular growth via its competitive binding to RAS. The mutation or elimination of RASSF1 will facilitate RAS-mediated cellular growth, further causing tumor occurrence (Tse et al, 2013;Zhou et al, 2014). This may be one of the mechanisms of RASSF1-mediated oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor suppressor gene RAS association domain family gene 1 (RASSF1) was identified in human chromosome 3p21.3 in 1982 (Whang-peng et al, 1982). The RASSF1 gene encodes RAS effective protein, which participates in RAS-related cellular signal pathways and regulates oncogenesis, cell differentiation, proliferation, and apoptosis of multiple malignant tumors (Zhou et al, 2014). Previous studies have revealed increased expression of RASSF1 in normal human tissues, while lower levels were observed in some tumor cells (e.g., lymphoma, pulmonary carcinoma, and melanoma), indicating some relationships between decreasing RASSF1 gene expression and tumor oncogenesis (Alkatan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[2] In common with most other tumour types the genesis of pituitary tumours is consequent to the combined contribution of genetic and epigenetic aberration, targeting the genome and epigenome respectively. [3,4,2,5] The relative contributions of these aberrations, their order of appearance, and the way in which their effects are manifest are largely unknown, however, specific aberration, be they genetic or epigenetic, are either common or particular to an adenoma subtype(s). [6,5,7] Moreover, the demarcation between genetic and epigenetic aberrations are perhaps less precise than initial findings suggested.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4,2,5] The relative contributions of these aberrations, their order of appearance, and the way in which their effects are manifest are largely unknown, however, specific aberration, be they genetic or epigenetic, are either common or particular to an adenoma subtype(s). [6,5,7] Moreover, the demarcation between genetic and epigenetic aberrations are perhaps less precise than initial findings suggested. In this context, we now know that the GNAS1 gene (the gsp oncogene), is activated or inappropriately expressed, either through mutation or relaxation of imprinting in growth hormone secreting pituitary adenomas.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies that investigated the effect of the MDM2 polymorphism on cancer development risk and prognosis. A large-scale study by Schmidt et al did not show any association between MDM2 SNP309T→G and p53 polymorphisms and breast cancer, whereas another study found a strong relationship between MDM2 SNP309T→G polymorphism and survival in patients with breast cancer (37,38). A study by Hirata et al involving patients with renal cell carcinoma showed that MDM2 polymorphism was associated with increased renal cell carcinoma risk.…”
Section: Discussionmentioning
confidence: 97%